2022
DOI: 10.1371/journal.pone.0277574
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance in shigellosis: A surveillance study among urban and rural children over 20 years in Bangladesh

Abstract: Antimicrobial resistance against shigellosis is increasingly alarming. However, evidence-based knowledge gaps regarding the changing trends of shigellosis in Bangladesh exist due to the scarcity of longitudinal data on antimicrobial resistance. Our study evaluated the last 20 years antimicrobial resistance patterns against shigellosis among under-5 children in the urban and rural sites of Bangladesh. Data were extracted from the Diarrheal Disease Surveillance System (DDSS) of Dhaka Hospital (urban site) and Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…After being the most preferred treatment option, CIP is seldom prescribed to treat Shigellosis in countries like Bangladesh currently because of its resistance mediated inefficiency 14 , 42 . In recent years, the prevalence of CIP resistance has been about 70% in patients of all ages, especially in Bangladesh 43 , 44 . In our study, we also found more than 70% CIP-resistance in 2016.…”
Section: Discussionmentioning
confidence: 99%
“…After being the most preferred treatment option, CIP is seldom prescribed to treat Shigellosis in countries like Bangladesh currently because of its resistance mediated inefficiency 14 , 42 . In recent years, the prevalence of CIP resistance has been about 70% in patients of all ages, especially in Bangladesh 43 , 44 . In our study, we also found more than 70% CIP-resistance in 2016.…”
Section: Discussionmentioning
confidence: 99%
“…In Bangladesh, surveillance of children under 5 years of age presenting with diarrhea to 2 hospitals during 2001–2020 showed resistance to ciprofloxacin increasing from essentially 0% of S. flexneri and S. sonnei clinical isolates in 2001–2005 to >70% resistant in 2016–2020. Resistance was worse for S. sonnei, with >90% of isolates resistant to ciprofloxacin [ 20 ]. Similar trends have been observed for azithromycin and ceftriaxone, though to different degrees.…”
Section: Shigella Burdenmentioning
confidence: 99%
“…In Vietnam, throughout a period of 14 years (1995–2008) S. sonnei cases increased from 29% to the 78% of Shigella isolations [ 23 ]. In Bangladesh, S. sonnei increased from around 10% of all Shigella cases in 2001 to nearly 50% in rural areas and over 50% in urban settings by 2020 [ 24 ]. More countries experiencing this phenomenon include Brazil [ 25 ], India [ 26 ], and Iran [ 27 ], among others.…”
Section: Epidemiologymentioning
confidence: 99%
“…Shigella infections are one of the major life-threatening hazards to which children from low- and middle- income countries, particularly in sub-Saharan Africa and South Asia, are exposed [ 3 , 23 , 24 , 82 , 85 ]. Shigella is the most prevalent cause of diarrhoeal illness among children between the ages of two and five, and the second most common cause in children below two years of age [ 86 ].…”
Section: Shigellosismentioning
confidence: 99%